Understanding Patient Safety Culture: the Role of Sociodemographic Factors Among Nursing Students in Malaysia - Noorsalfizah Jamil; Shalinawati Ramli; Nurul Azmawati Mohamed; Zarini Ismail (EL-MED-Pub Publishers, 2025)
Indexed